2007
DOI: 10.4161/cbt.6.10.4764
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of azoxymethane-induced colon cancer development in rats by dietary resistant starch

Abstract: Resistant starch is a complex carbohydrate that reaches the colon where it can be fermented by the colonic microflora resulting in production of short chain fatty acids (SCFA), in particular butyrate. RS effects on colorectal tumorigenesis are contrasting and protection remains controversial. Butyrate has an important role as the preferred metabolic fuel and regulator of colonocyte proliferation, differentiation and apoptosis and may play a role in cancer prevention. Thus variation in butyrate production from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…Our findings support previous data [9,39,40] emphasising how RS can reduce the proliferation and DNA alkyl adducts in the distal colon of wild-type rodents. We have also shown that functioning Msh2 protects against hyperproliferation and ACF formation in the colon, and that RS consumption protects against colonic hyperproliferation caused by the genetic defect of MMR.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings support previous data [9,39,40] emphasising how RS can reduce the proliferation and DNA alkyl adducts in the distal colon of wild-type rodents. We have also shown that functioning Msh2 protects against hyperproliferation and ACF formation in the colon, and that RS consumption protects against colonic hyperproliferation caused by the genetic defect of MMR.…”
Section: Discussionsupporting
confidence: 82%
“…Antineoplastic properties identified in vitro and in vivo highlight the butyrate's ability to increase the removal of highly damaged colon cells via apoptosis, as well as reducing cellular proliferation of the distal colon to allow for repair processes [41,42,43]. These effects of butyrate imply that it is responsible for reducing ACF and colon tumours in genetically normal rodents [39,44] although no such reduction was evident in non-carcinogenic models of spontaneous CRC [32]. Reduction of hyperproliferation by RS was not seen in the proximal colon, and this could be due to the rapid formation of SCFAs once RS reaches the proximal colon from the caecum, with a steady decline in SCFAs further along the colon [45].…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism through which high fiber diets decrease the risk of colon cancer is most likely due to increased production of butyrate by fermentation of dietary fiber in the intestine. Butyrate which is a short-chain fatty acid produced by dietary fiber fermentation in the colon is known as a chemoprotective agent [148]. …”
Section: Bioactive Dietary Components and Mirnamentioning
confidence: 99%
“…There is compelling evidence that butyrate causes a dose-dependent suppression of proliferation of colon cancer cell lines,48 and RS has antineoplastic effects against colon cancer in animal models 9 – 11. Recent studies in rat have shown that feeding RS reduced the incidence and multiplicity of azomethane-induced colon cancers and reduced the tumour-enhancing effects of indigestible protein and red meat 1214. These protective effects of RS were thought to be secondary to fermentation of RS to butyrate in the colon.…”
mentioning
confidence: 99%